Magnetoelectric Extracellular Vesicle Latency-Targeting (MELT) Nanotherapeutic for the Block-Lock-and-Kill HIV Eradication Strategy - Mickensone Andre; Nagesh Kolishetti; Adriana Yndart; Arti Vashist; Madhavan Nair; Andrea D. Raymond (Biomedicines)
Background: Human immunodeficiency virus (HIV) establishes latent infections in cellular reservoirs, including microglia. HC69 cells, a microglial model of HIV latency, contain an HIV promoter long terminal repeat (LTR)-GFP reporter and were used for testing the efficacy of a two-step magnetoelectric nanoparticle (MENP) and extracellular vesicle (xEV) latency-targeting (MELT) nanotherapeutic. GFP expression in HC69 at rest is low (GFPLo), and upon exposure to LTR, transcription-activating agents (i.e., TNF-α) are induced to be high expressing (GFPHi). Methods: The first step of MELT utilized ZL0580, an HIV Tat inhibitor loaded into EVs (80%) via incubation. ZL0580-EVs were taken up by GFPLo and blocked LTR transcriptional reactivation by 50% and were 90% less toxic than ZL0580 alone. The second step in MELT involved conjugation of monomethyl auristatin E (MMAE) to MENPs. HPLC measurements showed 80% MMAE attachment to MENPs. Flow cytometry-based measurements of the membrane potential indicated that the membranes of GFPHi HC69 were 60% more polarized than GFPLo HC69 cells. More MMAE–MENPs were internalized by GFPLo HC69. Results: Using a mixed-cell blood–brain barrier (BBB) Transwell model, we demonstrated that 20% of MELT crossed the BBB, was taken up by HC69 cells, and reduced LTR reactivation by 10%. Conclusions: Overall, this study demonstrated that MELT can potentially be utilized as a nanotherapeutic to target HIV latency in microglia.